Paul Bevan, trad. 2021. The Adventures of Ma Suzhen. “An Heroic Woman Takes Revenge in Shanghai”. Londres: Palgrave Macmillan. XIX + 131 pp. ISBN 9783030890377 - Haro Navejas, Francisco Javier (Estudios de Asia y África, 2025)
Paul Bevan, trad. 2021. The Adventures of Ma Suzhen. “An Heroic Woman Takes Revenge in Shanghai”. Londres: Palgrave Macmillan. XIX + 131 pp. ISBN 9783030890377